Distinctive alteration of presynaptic proteins in the outer molecular layer of the dentate gyrus in Alzheimer's disease. Issue 2 (13th May 2021) - Haytural, Hazal; Jordà-Siquier, Tomàs; Winblad, Bengt; Mulle, Christophe; Tjernberg, Lars O; Granholm, Ann-Charlotte; Frykman, Susanne; Barthet, Gaël
Abstract: Synaptic degeneration has been reported as one of the best pathological correlates of cognitive deficits in Alzheimer's disease. However, the location of these synaptic alterations within hippocampal sub-regions, the vulnerability of the presynaptic versus postsynaptic compartments, and the biological mechanisms for these impairments remain unknown. Here, we performed immunofluorescence labelling of different synaptic proteins in fixed and paraffin-embedded human hippocampal sections and report reduced levels of several presynaptic proteins of the neurotransmitter release machinery (complexin-1, syntaxin-1A, synaptotagmin-1 and synaptogyrin-1) in Alzheimer's disease cases. The deficit was restricted to the outer molecular layer of the dentate gyrus, whereas other hippocampal sub-fields were preserved. Interestingly, standard markers of postsynaptic densities (SH3 and multiple ankyrin repeat domains protein 2) and dendrites (microtubule-associated protein 2) were unaltered, as well as the relative number of granule cells in the dentate gyrus, indicating that the deficit is preferentially presynaptic. Notably, staining for the axonal components, myelin basic protein, SMI-312 and Tau, was unaffected, suggesting that the local presynaptic impairment does not result from axonal loss or alterations of structural proteins of axons. There was no correlation between the reduction in presynaptic proteins in the outer molecular layer and the extent of the amyloid load or of the dystrophic neurites expressing phosphorylated forms of Tau. Altogether, this study highlights the distinctive vulnerability of the outer molecular layer of the dentate gyrus and supports the notion of presynaptic failure in Alzheimer's disease. Abstract : Abbreviated summary Haytural et al. report that in Alzheimer's disease, the synaptic alterations within the hippocampus are preferentially affecting the outer molecular layer of the dentate gyrus whereas other hippocampal sub-regions are preserved. The decline in synaptic proteins is restricted to the presynapse and does not correlate with the amyloid load or neuritic phosphorylated-Tau. Graphical Abstract: